2023
DOI: 10.1039/d2ra07644f
|View full text |Cite
|
Sign up to set email alerts
|

Design strategies of Pt-based electrocatalysts and tolerance strategies in fuel cells: a review

Abstract: The latest developments of Pt-based electrocatalysts and their anti-CO poisoning mechanism are introduced. A brief perspective on the design of Pt-based electrocatalysts to inhibit CO poisoning in PEMFCs are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Platinum nanoparticles can also catalyze the oxygen evolution (OER) reaction, which is an important process for producing renewable fuels, such as hydrogen gas. In addition, platinum is also active toward the hydrogen reduction and oxidation reactions and many organic transformations. , Platinum’s versatility as a multifunctional catalyst is derived from the fact that its surface is capable of stabilizing a wide range of adsorbates within the potential windows required for effective electrocatalysis. Despite its effectiveness as a catalyst, the ongoing challenge in developing practical electrochemical devices is the high cost and low abundance of platinum.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum nanoparticles can also catalyze the oxygen evolution (OER) reaction, which is an important process for producing renewable fuels, such as hydrogen gas. In addition, platinum is also active toward the hydrogen reduction and oxidation reactions and many organic transformations. , Platinum’s versatility as a multifunctional catalyst is derived from the fact that its surface is capable of stabilizing a wide range of adsorbates within the potential windows required for effective electrocatalysis. Despite its effectiveness as a catalyst, the ongoing challenge in developing practical electrochemical devices is the high cost and low abundance of platinum.…”
Section: Introductionmentioning
confidence: 99%
“…Pt-based nanoparticles (NPs) alloyed with transition elements are being intensively studied, anticipating their potential use in catalysts as electrodes in fuel cell systems. [1][2][3][4][5][6][7][8][9][10] It is assumed that the improvement in the catalytic activity of Pt-based alloys is mainly due to lattice strain and the change in the electronic state of the d-electrons of Pt caused mainly by ligand effects. [10][11][12][13][14][15][16] In this regard, it was found that octahedral Pt 3 Ni NPs have an activity higher than 90 times that of pure Pt in the oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
“…According to identified reserves, the three traditional mineral resources, namely, coal, oil, and natural gas, are gradually becoming exhausted. Meanwhile, the issues of waste gas, the greenhouse effect, and ecological damage caused by the combustion of fossil fuels have become increasingly serious [ 1 , 2 , 3 , 4 , 5 , 6 ]. The recent outbreak of PM2.5 in China has alarmed the world.…”
Section: Introductionmentioning
confidence: 99%